Misuse of statistics in surgical literature - Thiese, Matthew S.; Ronna, Brenden; Robbins, Riann B. (Journal of Thoracic Disease, 2016)
Statistical analyses are a key part of biomedical research. Traditionally surgical research has relied upon a few statistical methods for evaluation and interpretation of data to improve clinical practice. As research methods have increased in both rigor and complexity, statistical analyses and interpretation have fallen behind. Some evidence suggests that surgical research studies are being designed and analyzed improperly given the specific study question. The goal of this article is to discuss the complexities of surgical research analyses and interpretation, and provide some resources to aid in these processes.